Looking for Biomarkers for Prostate Cancer Early Detection - Lu, PhD, Bin; Sanda, MD, Martin (North American Journal of Medicine and Science, 2009)
Cancer is a diverse disease and each cancer has different mechanism. To find a highly sensitive and specific biomarker that can reflect a single cancer, is a challenge for detection or therapeutic purpose. Gene expression profiling, proteomics, and immunology are used with increasing frequency as tools for cancer screening. The prostate-specific antigen (PSA) test is widely used as a screening test in prostate cancer. However, low specificity of serum PSA leads to many false-negative and false-positive results. We note that maintaining high specificity (low false-positive rates) is a very high priority for population screening. A small false-positive rate can translate into a large number of people who will suffer unnecessary costly further diagnosis and psychological stress. So, it is necessary that a biomarker of prostate cancer be both sensitive and specific.1 Beyond prognosis for prostate cancer, it is also very important to find molecular biomarkers correlating to prostate cancer disease progression. True et al. reported a molecular signature of 86 genes correlating to the Gleason grading system for prostate adenocarcinoma.2 Laxman showed a multiplex biomarker analysis of urine, which included six genes for prostate cancer detection.3 Recently, Chinnaiyan’s lab demonstrated a robust pipeline for the discovery of novel gene chimaeras by high-throughput sequencing.4 Metabolic profiling has shown a potential role for sarcosine in prostate cancer progression by using a combination of high-throughput liquid-and-gas-chromatography-based mass spectrometry in Chinnaiyan’s group.5